Proteomics and transcriptomics of peripheral nerve tissue and cells unravel new aspects of the human Schwann cell repair phenotype. Issue 12 (22nd August 2016) - Weiss, Tamara; Taschner‐Mandl, Sabine; Bileck, Andrea; Slany, Astrid; Kromp, Florian; Rifatbegovic, Fikret; Frech, Christian; Windhager, Reinhard; Kitzinger, Hugo; Tzou, Chieh‐Han; Ambros, Peter F.; Gerner, Christopher; et al.
Abstract : The remarkable feature of Schwann cells (SCs) to transform into a repair phenotype turned the spotlight on this powerful cell type. SCs provide the regenerative environment for axonal re‐growth after peripheral nerve injury (PNI) and play a vital role in differentiation of neuroblastic tumors into a benign subtype of neuroblastoma, a tumor originating from neural crest‐derived neuroblasts. Hence, understanding their mode‐of‐action is of utmost interest for new approaches in regenerative medicine, but also for neuroblastoma therapy. However, literature on human SCs is scarce and it is unknown to which extent human SC cultures reflect the SC repair phenotype developing after PNI in patients. We performed high‐resolution proteome profiling and RNA‐sequencing on highly enriched human SC and fibroblast cultures, control and ex vivo degenerated nerve explants to identify novel molecules and functional processes active in repair SCs. In fact, we found cultured SCs and degenerated nerves to share a similar repair SC‐associated expression signature, including the upregulation of JUN, as well as two prominent functions, i.e ., myelin debris clearance and antigen presentation via MHCII. In addition to myelin degradation, cultured SCs were capable of actively taking up cell‐extrinsic components in functional phagocytosis and co‐cultivation assays. Moreover, in cultured SCs and degenerated nerve tissue MHCII was upregulated at the cellular level along with high expression of chemoattractants and co‐inhibitory rather than ‐stimulatory molecules. These results demonstrate human SC cultures to execute an inherent program of nerve repair and support two novel repair SC functions, debris clearance via phagocytosis‐related mechanisms and type II immune‐regulation. GLIA 2016;64:2133–2153 Main points: Cultured human Schwann cells (SCs) share a similar repair SC‐associated expression signature with ex vivo degenerated nerves. We propose two novel repair SC functions: 1) debris clearance via phagocytosis and 2) a type II immune‐regulation.